Effect of monocular surgery for large-angle horizontal deviation in adults - Ganguly, S; Pradhan, R (Nepalese Journal of Ophthalmology, 2011)
Background: Surgical success rate of strabismus is variable. Objective: To evaluate the outcome of monocular strabismus surgery for adults with largeangle deviation. Subjects and methods: This study was that of a retrospective interventional case series. A total of 48 consecutive adult patients with large-angle socially-noticeable strabismus underwent clinical evaluation for squint surgery. They were divided into 2 groups of which 28 had exotropia while 20 had esotropia with deviation ranging from 40 to 80 prism diopters (PD). Visual acuity measurement (V/A), cycloplegic refraction and orthoptic evaluation were done in all cases along with detailed anterior segment evaluation. Fundus examination was carried out with indirect ophthalmoscope and slit-lamp bio-microscopy with + 90 D lens. For each case, a repeat evaluation was done after a six-week interval. The surgical procedure was monocular recession and resection carried out under peri-bulbar anesthesia by the same surgeon. Post-operative visual acuity, fusion, stereopsis and ocular alignment were noted in all cases during follow up visits. Results: Successful ocular alignment (< 10 PD) was achieved in 40 patients while binocularity was noted in 3. Forty patients were happy with the cosmetic outcome and psychosocial rehabilitation. No statistically significant improvement was noted in visual acuity and binocular function. Successful alignment was related to pre-operative deviation of less than 30 degrees. Conclusion: Monocular surgery under peri-bulbar anesthesia is a useful procedure for large-angle horizontal strabismus. Key words: strabismus; exotropia; esotropia; fusion; binocularity DOI: 10.3126/nepjoph.v3i1.4275 Nepal J Ophthalmol 2011;3(5):27-30